Targeting PRPK and TOPK for skin cancer prevention and therapy. Issue 42 (18th October 2018) - Roh, Eunmiri; Lee, Mee-Hyun; Zykova, Tatyana; Zhu, Feng; Nadas, Janos; Kim, Hong-Gyum; Bae, Ki; Li, Yan; Cho, Yong; Curiel-Lewandrowski, Clara; Einspahr, Janine; Dickinson, Sally; et al.
Abstract Solar ultraviolet (sUV) irradiation is a major environmental carcinogen that can cause inflammation and skin cancer. The costs and morbidity associated with skin cancer are increasing, and therefore identifying molecules that can help prevent skin carcinogenesis is important. In this study, we identified the p53-related protein kinase (PRPK) as a novel oncogenic protein that is phosphorylated by the T-LAK cell-originated protein kinase (TOPK). Knockdown of TOPK inhibited PRPK phosphorylation and conferred resistance to solar-simulated light (SSL)-induced skin carcinogenesis in mouse models. In the clinic, acute SSL irradiation significantly increased epidermal thickness as well as total protein and phosphorylation levels of TOPK and PRPK in human skin tissues. We identified two PRPK inhibitors, FDA-approved rocuronium bromide (Zemuron® ) or betamethasone 17-valerate (Betaderm® ) that could attenuate TOPK-dependent PRPK signaling. Importantly, topical application of either rocuronium bromide or betamethasone decreased SSL-induced epidermal hyperplasia, neovascularization, and cutaneous squamous cell carcinoma (cSCC) development in SKH1 (Crl: SKH1-Hr hr ) hairless mice by inhibiting PRPK activation, and also reduced expression of the proliferation and oncogenesis markers, COX-2, cyclin D1, and MMP-9. This study is the first to demonstrate that targeting PRPK could be useful against sUV-induced cSCC development.